1992
DOI: 10.3758/bf03199662
|View full text |Cite
|
Sign up to set email alerts
|

The discriminability of remembered magnitudes

Abstract: Psychometric functions and the associated indices of discriminative performance (i.e., the point of subjective equality [PSEl, just noticeable difference, and Weber fraction) were obtained with the method of constant stimuli using perceptual and remembered line-length standards. Three important results were obtained. First, comparisons with a perceptual or a remembered standard were sensitive to variations of absolute stimulus differences with a common ratio; that is, Weber's law was violated. Second, relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 58 publications
(73 reference statements)
5
27
0
Order By: Relevance
“…Specifically, in the near-far task, accuracy was higher when the farther distance was on the left; with lines, accuracy was higher when the longer line was on the right. Under the assumption that subjects acquire the stimuli in a left-to-right fashion (Masin & Agostini, 1991), the increased accuracy in the short, long presentation order in the present study is consistent with the typically observed negative time order error (TOE) for lines (Baranski & Petrusic, 1992), whereby accuracy is higher when the longer of two lines is presented second (cf. Dawes, 1980, Experiment 5, for a view of the effects on calibration of the TOE in a duration discrimination task).…”
Section: Presentation Order Effectssupporting
confidence: 76%
See 1 more Smart Citation
“…Specifically, in the near-far task, accuracy was higher when the farther distance was on the left; with lines, accuracy was higher when the longer line was on the right. Under the assumption that subjects acquire the stimuli in a left-to-right fashion (Masin & Agostini, 1991), the increased accuracy in the short, long presentation order in the present study is consistent with the typically observed negative time order error (TOE) for lines (Baranski & Petrusic, 1992), whereby accuracy is higher when the longer of two lines is presented second (cf. Dawes, 1980, Experiment 5, for a view of the effects on calibration of the TOE in a duration discrimination task).…”
Section: Presentation Order Effectssupporting
confidence: 76%
“…In fact, in all of our experiments employing the near-far task, we have been acutely aware that subjects might use the edge strategy, especially with the far pairs (see Petrusic, 1992;Petrusic & Baranski, 1989a, 1989b, 1997. Indeed, precisely in order to preclude the use of the edge of the screen, All subjectsweretold that becausethe fixationpoint varied from trial to trial (sometimes to the left of center, sometimes to the right), the edge of the screen did not provide a reliable cue for the nearer-farther judgment.…”
Section: Display Manipulation and The Edge Strategy A Reanalysis Of Bmentioning
confidence: 99%
“…Although there has been a great deal of research on the relationship between perceptual and memory effects, most of it has concentrated on the psychophysical aspects of perception and memory (e.g., Baranski & Petrusic, 1992;Bradley & Vido, 1985) or on the relationship between imagery and perception (Finke, 1980(Finke, , 1985Shepard, 1984). Few studies have examined serial position effects and their relationship to discrimination (but see Cacace et al, 1992;.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the extent of that value, we can extract important information that will help us to have more complete clinical features of early stages of perceptual and mental function conscious. Measures of variability sensory perception of linear behavior with the physical dimensions manipulated (Houstoun & Shearer, 1930;Stevens, 1957), functional capacity discriminating in comparison tasks (Baranski &Petrusic, 1992, Hanna, von Gierke, andGreen, 1986;Hecht, 1924;Mallery, Olomu, Uchanski, Militchin, & Hullar, 2010;Ross, 1997), perceptual measures of values for groups and populations (Deco & Rolls, 2006;Dzhafarov & Colonius, 2007;Sturzel & Spillmann, 2004, Warren, 2006 are just some examples of how information is psychophysical assessment and will be enriched as the clinical knowledge of diseases that affect mental processes, with the addition of a clinical psychology.…”
Section: Contributions On the Functional Assessmentmentioning
confidence: 99%